What Do Households Do when Things Are Rough?? Economic Situation, Pessimistic Economic Expectations and the Use of Livelihood Practices - Juliane Achatz; Anton Nivorozhkin; Markus Promberger; Brigitte Schels (Social Indicators Research, 2025)
This study investigates everyday practices that households utilize to improve or maintain their livelihoods. Drawing on prior qualitative research across various European economies, we developed a new survey tool, which was deployed within a larger survey encompassing the entire economic spectrum of German households. Using explorative factor analysis, we identified four overarching livelihood strategies employed by households: budget management, subsistence production, the liquidation of household assets, and the parsimonious procurement of essentials. Our results indicate a differential prevalence of these strategies, with a notable frequency among low-income households, although they are not exclusive to this group. The study reveals that both objective economic factors, such as income and material deprivation, and assessments of a household's past economic downturn and pessimistic future economic expectations influence the likelihood of adopting these livelihood strategies. However, certain indicators are more strongly predictive of specific strategies, such as parsimonious procurement of essentials is associated with lower household income and material deprivation while liquidation of household assets is closely associated with experiences of economic downturns.
Keywords: 300; Livelihood strategies; Household practices; Income gradient; Material deprivation; Pessimistic economic expectations